Site Investigation For Construction Of Emergency Spillway At The Jatigede Dam - I Gde Budi Indrawan; Gusti Imam Warman (Geological Engineering Department Universitas Gadjah Mada, 2015)
An emergency spillway has been planned to be constructed at the Jatigede Dam, West Java, to allow floodwater to flow downstream and to prevent the capacity of the main spillway to be exceeded during large flood events. The complex geology of theJatigede Dam area, however, poses a challenge to determine the suitable location for the emergency spillway construction, either in the area to the west or to the east of the embankment dam. An engineering geological mapping and landslide susceptibilityzoning were conducted to determine the engineeringgeological characteristics of the area surrounding theJatigede Dam. The site investigation showed that thearea to the west of the embankment dam tended tohave a lower slope inclination than the area to theeast of the embankment dam. Both areas to the westand to the east of the embankment dam were found tobe composed of less erosion resistant rock units. Theexistence of the earth retaining structures for slopestabilization in the area to the east of the embankment dam will, however, likely limit the flexibility in developing the emergency spillway route. With respect to the existence of fault systems, both areas to the west and to the east of the embankment dam will likely be influenced by similar conditions. The areato the west of the embankment dam tended to be lesssusceptible to landslide as compared to the area tothe east of the embankment dam. The undevelopedland use of the area to the west of the embankmen dam as compared to the area to the east of the embankment dam will provide more flexibility in construction of the emergency spillway. Due to the morefavorable engineering geological conditions, the area to the west of the embankment dam is proposed forthe location of the emergency spillway construction.Keywords: Emergency spillway, Engineering geological mapping, Jatigede Dam